Maria Guerrero and Fernando Diaz de Mendoza: the foundation of the Cervantes Theatre in Buenos Aires - Susana Shirkin (Teatro XXI, 1970)
This paper describes the foundation of the Cervantes Theatre in Buenos Aires at the initiative of the great Spanish actress María Guerrero and her husband, actor and aristocrat, Fernando Diaz de Mendoza. The venture was the culmination of a long relationship and affection that the Spanish couple had with Argentina since the late nineteenth century. It emphasizes the crucial role of Argentina’s elite, adherents of the “hispanismo”, both in the reception of the artist and her husband, as in the Cervantes Theatre construction project. Also, it analyzes the controversial purchase of the theatre by the Argentine government of Marcelo T. de Alvear and their policy implications.